KEMAMPUAN REPRESENTASI MATEMATIS SISWA DIKAJI DARI SELF-CONFIDENCE PADA MATERI PROGRAM LINEAR DI SMA - Theresia Eka Mubila Juniarti; Edy Yusmin; Asep Nursangaji (Universitas Tanjungpura, 2019)
AbstractThe importance of representation is also contained in the principles and standards of school mathematics evaluation. As much as 26% of students in class XI MIA-2 are completed and as much as 74% is declared incomplete. Based on the results of the study and the interview of three students the researcher suspected an indication of low student representation ability in linear program subject matter. There is a positive relationship between the self-concept of mathematics and the mathematical achievement one of them is self-confidence. The method used in this study is a quantitative descriptive with a form of survey research. Based on the self-confidence level, students who have high self-confidence tend to have high mathematical representation capabilities. The ability of mathematical representation of students who have high self-confidence has the ability to translate with 86% classified very high, while the ability of transformation with the achievement of 78% classified high. Students who have self-confidence in the translation capabilities with a 69% high classified ability, while the ability to transform with 47% of being classified is moderate. Students who have low self-confidence, have an ability to translate with 58% are classified as moderate, while the ability of transformation with 36% classified is low.Keyword: Ability, Mathematical Representation, Self-Confidence